Pengaruh Tingkat Upah dan Kualitas Sekolah Terhadap Permintaan Tenaga Kerja di Sektor Pendidikan di SMA Swasta Kota Jambi - Kuswanto; Anggi Yunita Sari; Muhammad Arif Liputo; Arpizal; Romi Kurniadi (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2024)
This study aims to determine the effect of wage level and school quality on labour demand in the education sector. The population in this study were 25 private high schools in Jambi City. This research is quantitative research with a survey method. Data collection techniques used dapodik data and questionnaires that went directly to schools. The data was analysed using multiple regression statistical techniques. The analysis shows that the wage level variable does not affect the demand for education sector labour. The higher the wage level, the more the company reduces the demand for education sector labour. School quality variable has a positive effect on labour demand. The better the quality of the school, the school will increase the demand for education sector labour. Simultaneously, wage level and school quality have a positive effect on labour demand. The higher the wage level and the better the school quality, the higher the labour demand in the education sector. The resulting regression model has a statistical ability of 36.9% in predicting the effect of wage level and school quality on education sector labour demand. Based on this finding, the demand for labour must be by the needs and expected output.